The Drosophila embryo as a tabula rasa for the epigenome. - Ahmad, K.; Henikoff, S. (Faculty reviews, 2022)
The control of gene expression in eukaryotes relies on how transcription factors and RNA polymerases manipulate the structure of chromatin. These interactions are especially important in development as gene expression programs change. Chromatin generally limits the accessibility of DNA, and thus exposing sequences at regulatory elements is critical for gene expression. However, it is challenging to understand how transcription factors manipulate chromatin structure and the sequence of regulatory events. The Drosophila embryo has provided a powerful setting to directly observe the establishment and elaboration of chromatin features and experimentally test the causality of transcriptional events that are shared among many metazoans. The large embryo is tractable by live imaging, and a variety of well-developed tools allow the manipulation of factors during early development. The early embryo develops as a syncytium with rapid nuclear divisions and no zygotic transcription, with largely featureless chromatin. Thus, studies in this system have revealed the progression of genome activation triggered by pioneer factors that initiate DNA exposure at regulatory elements and the establishment of chromatin domains, including heterochromatin, the nucleolus, and nuclear bodies. The de novo emergence of nuclear structures in the early embryo reveals features of chromatin dynamics that are likely to be central to transcriptional regulation in all cells.